2006
DOI: 10.1182/blood-2005-12-4831
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomes and marrow failure: coincidental association or molecular paradigm?

Abstract: IntroductionInherited bone marrow failure syndromes including dyskeratosis congenita (DC), cartilage-hair hypoplasia (CHH), DiamondBlackfan anemia (DBA), and Shwachman-Diamond syndrome (SDS) have long fascinated and challenged geneticists and hematologists. This heterogeneous group of disorders is characterized by bone marrow failure and the variable presence of congenital anomalies and cancer predisposition (Table 1). While there has been rapid progress in identifying gene defects in nearly all the disorders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 75 publications
3
116
0
3
Order By: Relevance
“…Moreover, other congenital syndromes have been linked to defective ribosome biogenesis, including Schwachman-Diamond syndrome (SDS), X-linked dyskeratosis congenita (DKC), cartilage hair hypoplasia (CHH), and Treacher Collins syndrome (TCS). 2 In the 5qϪ syndrome, a subtype of adult myelodysplastic syndrome, acquired haploinsufficiency for RPS14 resulting from an interstitial chromosomal deletion causes a severe refractory anemia. 3 Each of these disorders is associated with specific defects in ribosome biogenesis, which cause distinct clinical phenotypes, most often involving bone marrow failure and/or craniofacial or other skeletal defects.…”
Section: Identification Of Ribosomal Abnormalities In Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other congenital syndromes have been linked to defective ribosome biogenesis, including Schwachman-Diamond syndrome (SDS), X-linked dyskeratosis congenita (DKC), cartilage hair hypoplasia (CHH), and Treacher Collins syndrome (TCS). 2 In the 5qϪ syndrome, a subtype of adult myelodysplastic syndrome, acquired haploinsufficiency for RPS14 resulting from an interstitial chromosomal deletion causes a severe refractory anemia. 3 Each of these disorders is associated with specific defects in ribosome biogenesis, which cause distinct clinical phenotypes, most often involving bone marrow failure and/or craniofacial or other skeletal defects.…”
Section: Identification Of Ribosomal Abnormalities In Human Diseasementioning
confidence: 99%
“…Haploinsufficiencies for distinct ribosomal proteins have been linked to defects at distinct steps in pre-rRNA processing, which are outlined in Figure 1. 2 Several ribosomal proteins have extraribosomal functions, including replication and DNA repair, so mutations in ribosomal proteins may have effects that are independent of the protein translation machinery. 7,8 …”
Section: Overview Of Ribosome Biogenesismentioning
confidence: 99%
“…Many reports proved that the errors of progress in the ribosomal biogenesis were the cause of the various diseases. The inherited bone marrow failure syndromes representatively showed a close relationship between p53-mediated cell growth regulation and cellular responses to abnormality of ribosome synthesis (Liu and Ellis, 2006). Interestingly, in zebrafish, it was suggested that aberrant ribosome biogenesis through the mutation of ribosomal genes has an oncogenic potential (Amsterdam et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This occurs, for example, in the case of conditional deletion of RPS6 (Volarevic et al, 2000;Sulic et al, 2005) or in response to drugs that disrupt nucleolar structures (Rubbi and Milner, 2003). Alteration of ribosome synthesis has also been implicated in some pathologies that are associated to mutations in ribosomal components, for instance, Diamond-Blackfan anemia (DBA), or in molecules involved in ribosome maturation (reviewed by Liu andEllis, 2006 andCaldarola et al, 2009).…”
Section: Introductionmentioning
confidence: 99%